Information Costs and Location of FDIs within the Host Country: Empirical Evidence from Italy - Mariotti, Sergio; Piscitello, Lucia (Journal of International Business Studies, 1995)
The literature on foreign direct investments (FDIs) has analysed the location strategies of multinational enterprises across national borders, but there have been few studies of location decisions by foreign investors within the borders of a single country. The paper argues that the driving factors of these location choices have differing influences on indigenous and foreign investors. Specifically, foreign investors suffer from a condition of adverse asymmetry in information costs compared to insiders. Thus, foreign investors' decisions on the location of their activities within a host country mainly reflect a rational responses to the existence of information costs.